2017
DOI: 10.1590/0102-33062017abb0001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some environmental factors on seed germination of Eryngium caeruleum M. Bieb. populations

Abstract: Th e eff ects of alternating and constant temperatures and light regimes, osmotic and salt stress and pH were tested on seed germination in four populations of Eryngium caeruleum. Laboratory experiments revealed that the four populations exhibited diff erent responses to alternating temperature and light conditions. Alternating temperature and photoperiod had a greater positive eff ect on seed germination compared to complete darkness. Th e optimal constant temperature within 10 ºC to 15 ºC for seed germinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
(24 reference statements)
0
7
0
2
Order By: Relevance
“…Menurut (Purwanto et al, 2021;Ifansyah, 2014), masalah umum pada tanah masam seperti ultisols adalah pH dan kesuburan yang rendah, ketersediaan unsur P dan bahan organk yang rendah, dan Al + yang tinggi. Tanah masam menyebabkan penurunan perkecambahan, terhambatnya pertumbuhan tanaman, dan rendahnya produktivitas tanaman (Gentili et al, 2018;Herison et al, 2020;Rezvani & Zaefarian, 2017). Pada tanaman padi cekaman aluminium pada tanah Ultisol menyebabkan penghambatan akar primer dan rambut akar (Alvarez et al, 2012;Aprilliani et al, 2017).…”
Section: Pendahuluanunclassified
“…Menurut (Purwanto et al, 2021;Ifansyah, 2014), masalah umum pada tanah masam seperti ultisols adalah pH dan kesuburan yang rendah, ketersediaan unsur P dan bahan organk yang rendah, dan Al + yang tinggi. Tanah masam menyebabkan penurunan perkecambahan, terhambatnya pertumbuhan tanaman, dan rendahnya produktivitas tanaman (Gentili et al, 2018;Herison et al, 2020;Rezvani & Zaefarian, 2017). Pada tanaman padi cekaman aluminium pada tanah Ultisol menyebabkan penghambatan akar primer dan rambut akar (Alvarez et al, 2012;Aprilliani et al, 2017).…”
Section: Pendahuluanunclassified
“…Peristiwa hidrolisis pada tanah Kondisi ini sejalan dengan penelitian yang dilakukan pada populasi Eringium caeruleum, diperoleh nilai germination index yang paling tinggi pada pH 7. 14 Faktor-faktor lingkungan yang diamati pada penelitian tersebut diantaranya adalah pH, temperatur, kadar garam, dan proses inkubasinya (gelap/terang). Kondisi pH tinggi atau rendah konsentrasi H + , makronutrien tidak terlalu kuat ikatannya dengan permukaan tanah sehingga masih memungkinkan ketersediaan untuk serapan oleh tanaman, dan lebih banyak ketersediaannya dibandingkan pada kondisi pH rendah.…”
Section: Hasil Dan Pembahasanunclassified
“…The first is the bioconcentration factor that indicates the efficacy of a plant species to accumulate a heavy metal from the contaminated soil in its tissues and is expressed by the ratio of the concentration of the metal accumulated in the harvested plant biomass to the concentration of the same metal in the soil. The second factor is the translocation factor that indicates plant efficiency in translocating accumulated metal from roots to shoots and is expressed as the ratio of the metal concentration in plant shoots to the metal concentration in plant roots [54] A successful phytoextraction is conditioned by increased values of these two parameters, combined with increased metal xylem loading and detoxification of metals in plants [9]. Physiological studies showed that heavy metal xylem loading and its transfer to aerial parts of plants is mediated by a series of transport proteins that are in most cases found in plasma or intracellular membranes [52].…”
Section: Phytoextractionmentioning
confidence: 99%